A metodologia do sensível: o processo de projeto de audiovisualidades - Pedrozo, Danielle Difante (Universidade do Vale do Rio dos Sinos, 2022)
The interest in investigating the creative process of narratives focused on audiovisual products also led to a reflection on how design could re-semanticize its projects, by giving more relevance to the subjectivities of subjects and to aesthetic values. In this sense, sensoriality stands out, as it is perception that mediates the encounters between subjects and objects. Thus, a methodology aimed at creating sensitive products (audiovisualities) was designed. For this, we sought to explore the creative process in the treatment of narratives, in order to promote their potential to touch/affect the audience. In addition, a series of practical, inaugural and subjective experiences were developed, inspiring by the creative nature of their processes. The assumed method is empirical inductive of an experimental nature, visiting reality through a series of experiences that are characterized by their uniqueness and unpredictability, becoming an open space for reflection and transformation. The bibliographic review, together with visual and sound recordings, also constituted the basis for the knowledge production process. The methodology of the sensitive showed that its functioning is an eternal movement of interpreting and reinterpreting, which happened individually or collectively. That is why sensitive practices were not interested in the linear translation of narratives, but in the creative exercise of inventing countless possibilities to update and re-signify them through the proposed processes. The act of creation was linked to sensible matter. The methodology of the sensitive also asserted itself as a theory, due to its set of ideas (and ideals).
Keywords: Design; Semiótica; Audiovisualidades; Complexidade; Metodologia; Semiotics; Audiovisualities; Complexity; Methodology; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial